Histological Observation Related to the Use of Laser and Ultrasound on Bone Fracture Healing - MF, Al-Habib; MO, Salman; FW, Faleh; IM, Al-Ani (IIUM Medical Journal Malaysia, 2011)
Objective: To study the effect of both laser and ultrasound radiation on bone fracture healing process. Materials and Methods: Nd:YAG laser (1064 nm wavelength, 135 mW power, 16 joules energy) and ultrasound (1 MHz frequency, 50 mW/cm2 power intensity) were used in this work. Fifteen mature, male, albino rats, were divided into three groups and subjected to a partial fracture on the lateral aspect of femur by a sharp blade. The fi rst group of these animals served as control group. The second group was illuminated by the Nd:YAG laser for two minutes; the fi rst dose was given immediately after surgical fracture induction; the other doses were given on days two, three, six and then one dose weekly for the next three weeks while the third group were treated by the addition of the CW ultrasound perpendicular to the laser treatment in the second group. Results: The present study showed that ultrasound increases the penetration of laser power through the tissue. The histological assessments at day 28 after the fracture of fi rst group showed incomplete healing of the bone with disfi guration and disarrangement of Haversian system and the periosteum was not yet well developed. Treatment with laser showed irregularity and lack of Haversian system formation in bone healing of the second group. The laser and ultrasound treated group (third group) expressed a complete healing at the site of fracture with a complete layer of periosteum and a well arranged Haversian system. Conclusion: Combination of laser and ultrasound in therapy can enhance healing process of a fractured bone more than laser therapy alone, as ultrasound increases the depth of laser penetration in tissue.